Retrofitting of Masonry Vaults by Basalt Textile-Reinforced Mortar Overlays. Issue 7 (3rd October 2019) - De Santis, Stefano; de Felice, Gianmarco; Roscini, Francesca
ABSTRACT: In a period characterized by the urgent need of enhancing the safety level of the building stock, including architectural heritage, externally bonded textile-reinforced mortar (TRM) systems are emerging as a particularly advantageous strengthening solution. Their use on unreinforced masonry arched members appears one of the most promising fields of application, but an improved understanding still needs to be gained on the behavior of TRM retrofitted interstorey vaults. This article describes an experimental investigation on full-scale masonry vaults, provided with buttresses and backfill, reinforced with basalt textile-reinforced mortar (BTRM) overlays either at the intrados or at the extrados. Cyclic load was applied at 1/3 span over the backfill. Digital Image Correlation was used to detect full-field displacements and map crack development. Both strengthening solutions proved effective in delaying crack occurrence and improving arch-fill interaction, enhancing both load-carrying and deflection capacity. A limit analysis-based method provided reliable ultimate strength estimates for engineering design and assessment purposes.